Uncovering individual training-load profiles in young female footballers: moving beyond the average - Los Arcos, A.; Gonzalez-Artetxe, A.; Beato, M.; Garcia-Tabar, I. (International Journal of Sports Physiology and Performance, 2026)
Purpose: To assess total, weekly, and session rating of perceived exertion (sRPE) training load (TL), identify factors influencing sRPE-TL, and analyze interplayer, individual relative-to-team, and intraplayer variability in elite youth female footballers. Methods: All outfield players (age 13.7 [0.5] y) from the U14 (under 14 y of age) team of a Spanish Women`s First Division academy were monitored over a 19-week competitive period. Players reported sRPE after each training session and match. TL was calculated as sRPE × session duration. Individual- and team-level analyses were performed. Results: Players completed 95% (4%) of sessions. Total and weekly team sRPE-TL averaged 19,717 (1708) and 1200 (104) AU (arbitrary units), respectively. Playing position had no significant effect (P > .05), whereas training day significantly influenced session TL (P < .001), with matches showing substantially lower TL than training sessions (Cohen d: 2.85-4.34). Interplayer variability was small to moderate (coefficient of variation 7%-14%). Differences between individual and team means ranged from -26% to +25%, trivial to very large. Intraplayer variability was moderate to very large (coefficient of variation 10%-53%), with session-level variability classified as very large for all players. The interaction between individual-team difference and intraplayer variability was analyzed. Conclusions: Despite consistent team-level TL, marked individual differences emerged. Two individual TL profiles were identified: (1) mean-aligned versus mean-divergent and (2) stable versus unstable. Combining both dimensions enhances individual TL profiling and supports tailored training strategies. These findings emphasize the need to move beyond team averages to ensure appropriate monitoring and individualized development in elite youth female football.